Colonial Knowledge and the Emergence of Public Nutrition in Colonial Indonesia (1930s–1940s) - Mafa'idah, Rizka Salsabila (Analisis Sejarah, 2026)
This article analyzes the transformation of nutritional knowledge in Indonesia during the 1930s to 1940s, which shifted from concerns about food supply to issues of nutrition. The economic crisis prompted the colonial government to recognize the decline in the quality of food consumption among the population, caused by various factors. Consequently, the colonial authorities adopted new approaches to understand nutritional problems in society. The central question of this study is how the colonial state translated laboratory-based nutritional science into a systemic bureaucratic tool to manage the population’s biological welfare during a period of global crises. This study employs historical research methods and applies a public nutrition approach. The findings show the shift from food supply to public nutrition and the institutionalization of nutritional knowledge through colonial bureaucracy. Thus, nutritional problems can no longer be understood merely as biological issues but must be seen as social phenomena related to economic conditions and patterns of consumption. This shift reflects a new understanding by the colonial state in conceptualizing the welfare of the population through scientific knowledge. Finally, this study implies that the institutionalization of nutrition served as a fundamental element of late-colonial state formation, where scientific knowledge was integrated into the mechanisms of administrative control and social engineering.